2009
DOI: 10.1111/j.1439-0418.2008.01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and molecular characterization of distinct Asian populations of Bemisia tabaci (Hemiptera: Aleyrodidae) in Japan

Abstract: Bemisia tabaci (Gennadius) is considered to be the most economically important pest insect worldwide. The invasive variant, the Q biotype of B. tabaci was first identified in 2004, and has caused significant crop yield losses in Japan. The distribution and molecular characterization of the different biotypes of B. tabaci in Japan have been little investigated. In this study, B. tabaci populations were sampled from the Japanese Archipelago, the Amami Archipelago and the Ryukyu Islands between 2004 and 2008, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 39 publications
4
48
1
Order By: Relevance
“…Currently, the COI phylogeny supports at least seven major phylogeographic clades (Fig. 2.7a, b), while the phylogenies based on the mitochondria16S and the ribosomal intergenic spacer 1 (ITS1), although not as well resolved, do reflect a phylogeography similar to the COI tree (Berry et al 2004;Boykin et al 2007;De Barro et al 2005;Frohlich et al 1999;Kirk et al 2000;Sseruwagi et al 2005Sseruwagi et al , 2006Ueda et al 2009). The latter two markers differ primarily with respect to extent of genetic variation, with the COI being more divergent than the others (Boykin et al 2007;Frohlich and Brown 1994;Frohlich et al 1996Frohlich et al , 1999.…”
Section: From Concept To Working Definitionmentioning
confidence: 96%
See 1 more Smart Citation
“…Currently, the COI phylogeny supports at least seven major phylogeographic clades (Fig. 2.7a, b), while the phylogenies based on the mitochondria16S and the ribosomal intergenic spacer 1 (ITS1), although not as well resolved, do reflect a phylogeography similar to the COI tree (Berry et al 2004;Boykin et al 2007;De Barro et al 2005;Frohlich et al 1999;Kirk et al 2000;Sseruwagi et al 2005Sseruwagi et al , 2006Ueda et al 2009). The latter two markers differ primarily with respect to extent of genetic variation, with the COI being more divergent than the others (Boykin et al 2007;Frohlich and Brown 1994;Frohlich et al 1996Frohlich et al , 1999.…”
Section: From Concept To Working Definitionmentioning
confidence: 96%
“…In summary, the greatest diversification for the B. tabaci sibling species group based on a rather extensive, though incomplete, representation of haplotypes appears to be either sub-Saharan Africa (Berry et al 2004;Boykin et al 2007; De la Rúa et al 2006;Hsieh et al 2006;Sseruwagi et al 2005Sseruwagi et al , 2006 or Asia (Brown and Idris 2005;Qiu et al 2007;Ueda et al 2009). There is good evidence that genetic variation is low in the Western Hemisphere, where both inter-and intra-population divergence and differentiation estimates are very low (Boykin et al 2007;Brown and Idris 2005;Viscarret et al 2003;Zhang et al 2005;Hadjistylli et al Chapter 3).…”
Section: Selection and Differentiationmentioning
confidence: 97%
“…Most biotypes, however, have only been designated based on difference of molecular markers, without any consistent biological characterization, and should be regarded more properly as haplotypes (Brown 2010) or genetic variants (De Barro et al 2011). Most genetic variants of B. tabaci are confined to specific geographic regions, but some of them, namely the well-characterized B and Q biotypes, are distributed worldwide raising the status of global pests (Brown 2007;Ueda et al 2009). The strong biological and genetic differentiation and the occurrence of incompatible matings between populations with different genotype have led to consider B. tabaci a complex of cryptic species (Perring 2001;Boykin et al 2007;Brown 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Biotype Q, recorded for the first time at the beginning of 1990s in Spain (Guirao et al 1997), has become a major pest in European Mediterranean regions, North Africa and Israel (Horowitz et al 2003;Simón et al 2007;Tsagkarakou et al 2007), and most recently, it has spread in the North and Central America, in East Asia and New Zealand (Chu et al 2007;Martinez-Carrillo and Brown 2007;Ueda et al 2009). Both biotypes, owing to their characteristics of strong polyphagy, high reproductive rate and high level of resistance to insecticides (Olivera et al 2001;Horowitz et al 2005;Roditakis et al 2005;Bonato et al 2007) represent a serious threat to cultivated plants in any area of invasion.…”
Section: Introductionmentioning
confidence: 99%
“…However, this estimate is still uncertain because not all of the COI sequences of B. tabaci were included in these studies (i.e., Dinsdale et al [9], Chowda-Reddy et al [11], Alemandri et al [12], and Hu et al [13]). For example, Ueda et al [15] reported one putative new species, JpL , of the B. tabaci complex; however, COI sequences of the JpL species have not been considered in the subsequent calculations of the number of species in the B. tabaci complex [9].…”
Section: Introductionmentioning
confidence: 99%